Observing grooming promotes affiliation in Barbary macaques. Issue 1893 (12th December 2018) - Berthier, Juliette M.; Semple, Stuart
Abstract : Observing friendly social interactions makes people feel good and, as a result, then act in an affiliative way towards others. Positive visual contagion of this kind is common in humans, but whether it occurs in non-human animals is unknown. We explored the impact on female Barbary macaques of observing grooming, a behaviour that physiological and behavioural studies indicate has a relaxing effect on the animals involved. We compared females' behaviour between two conditions: after observing conspecifics groom, and in a matched control period. We found that observing grooming was associated with reduced behavioural indicators of anxiety, suggesting that seeing others groom is, in itself, relaxing. Observing grooming was also associated with a shorter latency to becoming involved in a grooming bout (and higher likelihood both of initiating that bout and being the groomer rather than groomee), and with elevated rates of other affiliative behaviours. These results provide evidence for positive visual contagion; this phenomenon may contribute fundamentally to group cohesion not just in this species, but also in the many mammal and bird species where grooming occurs. Our study highlights the importance of exploring social behaviour beyond the level of the interacting individuals, within the broader social context where it occurs.